Herbal medication triggering lupus nephritis - a case report - Abdul Rashid, Anna Misya’il; Abd Ghani, Fauzah; Inche Mat, Liyana Najwa; Thiam, Christopher Seong Lim (BioMed Central, 2020)
Background: Herbal medication is widely used in our region as a mode of alternative medicine. Its contents and combinations are often modified to suit the needs of different populations. These products are said to boost the immune system and may serve as a protective measure against many diseases including Systemic Lupus Erythematosus (SLE). Some even lay claims to be able to cure SLE. Although they are not without side effects, these medications are still preferred due to their widespread availability and affordability, compared to modern medications. However, to date, there have been no reported cases in which these traditional medications can trigger a lupus-like reaction, moreover one involving the kidneys. Case presentation: We report a patient who developed overt lupus nephritis after consuming a course of herbal supplement. Her renal status did not improve upon cessation of the offending drug, and she required immunosuppressive therapy. After one cycle of IV cyclophosphamide, we managed to get the patient into remission - she is now on tapering doses of steroids. Conclusion: We wish to highlight the possibility of consumption of herbal medication and the emergence of drug-induced lupus nephritis. A thorough anamnesis and high index of suspicion of drug-induced lupus nephritis is warranted when a patient on supplements presents with urinary abnormalities.